Type 1 Diabetes in Acute Pancreatitis Consortium: From Concept to Reality. Issue 6 (July 2022) - Serrano, Jose; Laughlin, Maren R.; Bellin, Melena D.; Yadav, Dhiraj; Chinchilli, Vernon M.; Andersen, Dana K.
Abstract: Acute pancreatitis (AP), resulting from inflammation of the pancreas, accounts for more than 300, 000 US hospital discharges per year. Although glucose intolerance has been known as a complication of severe AP, this effect was thought to be transient. Recently, cohort studies and meta-analysis of 24 published studies of 1100 patients who survived one or more episodes of AP revealed that 30% to 40% of patients developed diabetes or impaired glucose tolerance within 3 to 4 years of even a single episode of AP. The National Institute of Diabetes and Digestive and Kidney Diseases funded the Type 1 Diabetes in Acute Pancreatitis Consortium (T1DAPC) to undertake a prospective observational study of the occurrence of diabetes during an AP episode or subsequently, with emphasis on type 1 diabetes. Key factors for funding T1DAPC are the increasing incidence and prevalence of AP, its association with the development of type 1 diabetes and other forms of diabetes after AP, its complications, and associated health care cost. The T1DAPC structure, governance, and research objectives are described in this article. The DREAM (Diabetes RElated to Acute pancreatitis and its Mechanisms) studies to be undertaken by the T1DAPC are described in other articles in this journal's issue.